2015
DOI: 10.1155/2015/948674
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing Spondylitis and Posture Control: The Role of Visual Input

Abstract: Objectives. To assess the motor control during quiet stance in patients with established ankylosing spondylitis (AS) and to evaluate the effect of visual input on the maintenance of a quiet posture. Methods. 12 male AS patients (mean age 50.1 ± 13.2 years) and 12 matched healthy subjects performed 2 sessions of 3 trials in quiet stance, with eyes open (EO) and with eyes closed (EC) on a baropodometric platform. The oscillation of the centre of feet pressure (CoP) was acquired. Indices of stability and balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 40 publications
1
14
1
1
Order By: Relevance
“…When the eyes were closed, the oscillations were wide and were low velocity in the anteroposterior direction for healthy subjects, and they were rapid and had high amplitude in the patients with AS. The researchers surmised that the patients with AS were more likely to rely on visual input for sustaining the balance and that there was increased worsening in balance compared to healthy subjects when their eyes were closed [26]. The authors suggested that this change, which occurred without pathology in the central nervous system or visual pathway, could indicate impaired motor control or problems in the feedback mechanisms from lower extremity muscles.…”
Section: Visual Systemmentioning
confidence: 99%
“…When the eyes were closed, the oscillations were wide and were low velocity in the anteroposterior direction for healthy subjects, and they were rapid and had high amplitude in the patients with AS. The researchers surmised that the patients with AS were more likely to rely on visual input for sustaining the balance and that there was increased worsening in balance compared to healthy subjects when their eyes were closed [26]. The authors suggested that this change, which occurred without pathology in the central nervous system or visual pathway, could indicate impaired motor control or problems in the feedback mechanisms from lower extremity muscles.…”
Section: Visual Systemmentioning
confidence: 99%
“…There are studies that use the tandem walking test, step and quick turn test (22), the force platform (23), and Biodex balance This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as: Karahan www.erciyesmedj.com system (24) to assess static and dynamic balance in AS patients (9). In this study, the tests were performed with eyes open and eyes closed to investigate the effects of visual input.…”
Section: Discussionmentioning
confidence: 99%
“…The most important clinical feature of the disease is the distorted posture of the spine (8). Patients with poor posture may have balance problems (9). The head and face tilt downward as a result of advanced thoracolumbar kyphosis (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okrem pozitívnych metabolických vplyvov, dôležitú úlohu zohráva cvičenie aj pri zlepšení spinálnej mobility a svalovej sily. Udržanie správneho posturálneho držania javí kľúčovú úlohu u pacientov s ankylozujúcou spondylitídou (14)…”
Section: Cvičenie Má Významný Vplyv Na Index Telesnej Hmotnosti (Bmi)unclassified